2016
DOI: 10.1155/2016/1656450
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Myocardial Ischemia and Reperfusion Injury and Remodeling: Revisited

Abstract: Oxidative and reductive stress are dual dynamic phases experienced by the cells undergoing adaptation towards endogenous or exogenous noxious stimulus. The former arises due to the imbalance between the reactive oxygen species production and antioxidant defenses, while the latter is due to the aberrant increase in the reducing equivalents. Mitochondrial malfunction is the common denominator arising from the aberrant functioning of the rheostat that maintains the homeostasis between oxidative and reductive stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(188 citation statements)
references
References 136 publications
5
175
0
1
Order By: Relevance
“…Oxidative stress has a central role in the pathophysiology of MIRI [6,26]. Myocardium undergoing ischemic injury followed by re-establishment of the blood supply generate superabundant oxygen free radicals, triggering oxidative stress, aggravating MIRI, and eventually resulting in mitochondrial dysfunction, cell damage, apoptosis, and necrosis [4].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress has a central role in the pathophysiology of MIRI [6,26]. Myocardium undergoing ischemic injury followed by re-establishment of the blood supply generate superabundant oxygen free radicals, triggering oxidative stress, aggravating MIRI, and eventually resulting in mitochondrial dysfunction, cell damage, apoptosis, and necrosis [4].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…Myocardium undergoing ischemic injury followed by re-establishment of the blood supply generate superabundant oxygen free radicals, triggering oxidative stress, aggravating MIRI, and eventually resulting in mitochondrial dysfunction, cell damage, apoptosis, and necrosis [4]. The bioactive gas, NO, has pro-survival effects that can relieve myocardial I/R injury by scavenging oxygen free radicals, reducing thrombus formation caused by platelet activation, and regulating leukocyte mediated inflammation [26,27]. Increases in the production of NO by activation of eNOS (an enzyme responsible for the production of NO) exert protective effects in reducing the size of myocardial infarcts and improving cardiac function in I/R hearts [28].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
“…The antioxidant enzymes, SOD, GSH-PX and CAT in myocardial cells can remove the reactive oxygen species produced during oxidative stress, but the excessive ROS generated during I/R overwhelm these enzymes and weaken the body's antioxidant capacity [11,12]. In this study, analysis of the serum levels of MDA and antioxidant enzymes showed that serum SOD, GSH-PX and CAT levels of the I/R group were significantly lower than those of negative control group while MDA level was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The drug meksikor ("MiraxBioPharma") was administered at the dose of 85.72 mg/kg/day. [7] The modeling of hypo/ reperfusion was performed on a rat heart isolated by Langendorf.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] Modern pharmacotherapy of cardiovascular diseases as a supplementary therapy can recommend natural antioxidants (vitamin E, C, A and carotenoids, resveratrol, and L-carnitine), and more often, synthetic ones such as trimethylhydrazinium propionate (mildronate) derivatives, as well as heterocyclic analogs of aromatic phenols, the derivatives of 3-hydroxypyridine (mexicor, emoxipin, and mexidol) with a number of other pharmacological effects important for complex treatment of the cardiovascular system (endothelioprotective, preconditioning, and antihypoxic). [3][4][5][6] In this regard, the purpose of this study was to study the cardioprotective effects of new 5-hydroxynicotinic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%